(untitled) (Web of Teachers: Inderscience Research, 2024)
The development and efficiency of fruit and vegetable clusters play a crucial role in regional economic growth and the improvement of agricultural practices. This study assesses the current state of fruit and vegetable clusters, identifying strengths and areas for development, and proposes strategies to enhance their functionality. The analysis emphasizes the importance of coordinated efforts, innovation, and sustainable practices to ensure competitive and profitable agricultural production.